2012
DOI: 10.1039/c2sm25537e
|View full text |Cite
|
Sign up to set email alerts
|

Formation of the block copolymer aggregates via polymerization-induced self-assembly and reorganization

Abstract: The self-assembly of block copolymers attracts wide interest due to many potential applications of the polymeric aggregates. Great effort has been made to realize the convenient fabrication of abundant polymeric materials with well-defined nanostructures. This review introduces the development of the in situ preparation of block copolymer aggregates by heterogeneous polymerization. Great emphasis is put on discussing the formation mechanism of aggregates with different morphologies. Some important factors that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
130
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(135 citation statements)
references
References 65 publications
(23 reference statements)
2
130
0
3
Order By: Relevance
“…[ 10,12,21,29 ] It rather provides guidelines for helping non-specialists in conducting successful RAFT dispersion polymerization for producing various self-assembled morphologies.…”
Section: Introductionmentioning
confidence: 99%
“…[ 10,12,21,29 ] It rather provides guidelines for helping non-specialists in conducting successful RAFT dispersion polymerization for producing various self-assembled morphologies.…”
Section: Introductionmentioning
confidence: 99%
“…25 1 H NMR spectra were recorded in either CD 2 Cl 2 or CDCl 3 using a Bruker AV1-400 or AV1-250 MHz spectrometer. Typically sixty four scans were averaged per spectrum.…”
Section: Gel Permeation Chromatographymentioning
confidence: 99%
“…Currently, there is strong academic interest in polymerization- 25 induced self-assembly (PISA) [1][2][3] using living radical polymerization techniques such as reversible additionfragmentation chain transfer (RAFT) polymerization. [4][5][6][7][8] This approach has enormous potential for the design of bespoke - 30 any further processing steps.…”
Section: Introductionmentioning
confidence: 99%
“…Micelles, which are micro-or nanoscale globular particles, are prepared by amphiphilic block co-polymers and can carry several guest molecules at the core region. The size selection of micelles is achieved by centrifuging the samples at different speed [61]. Popere et al [62] reported that micelles, which were formed by copolymer polystyrene-block-poly(4-vinylpyridine)…”
Section: B Doping Concentration Control By Monolayer Dopingmentioning
confidence: 99%